Language Assessment of Latino English Learning Children: A Records Abstraction Study. Issue 4 (2nd October 2017) - Kraemer, Robert; Fabiano-Smith, Leah
ABSTRACT: The researchers examined how speech-language pathologists (SLPs) in a small northern California school district assessed Spanish speaking English learning (EL) Latino children suspected of language impairments. Specifically we sought to (1) determine whether SLPs adhered to federal, state, and professional guidelines during initial assessments and (2) identify tests and measures used by SLPs during language assessments. The researchers conducted a records abstraction review of 88 speech-language assessment reports of Spanish speaking EL Latino children. The reports were examined for parameters of best practice as outlined in recent studies. Results indicated that for each report the SLP responsible for assessing the child failed to consider at least one best practice parameter. Although impossible to determine at this stage, it is likely that many of these children were erroneously assessed and subsequently placed in speech-language programs. Findings support the notion that many EL Latino children continue to be inappropriately assessed for language impairments.